Global Implications of U.S. Tax Reform - Jack Mintz (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Tax reform adopted in United States for 1 January, 2018 will have a significant positive impact on the global economy in 2018. The ground-breaking corporate income tax will also substantially affect US tax competitiveness with many provisions drawing both capital and profits to the United States. With the sharply lower corporate income tax rate, dividend exemption system and new limitations on deductible interest, US companies will try to push debt and other costs onto foreign countries, reducing corporate taxes elsewhere. This paper outlines key facts on the corporate tax reform featured in the US Tax Cuts and Jobs Act, assesses the reform with respect to US investment and examines the impacts of interest and loss limitation rules, as well as new US taxes with respect to intangible income.
Keywords: 330